2017
DOI: 10.1007/s00264-017-3625-9
|View full text |Cite
|
Sign up to set email alerts
|

Viscosupplementation in patients with severe osteoarthritis of the knee: six month follow-up of a randomized, double-blind clinical trial

Abstract: Viscosupplementation increased functional scores in patients with severe osteoarthritis of the knee, especially within three months of injection. However, it was not superior to the use of triamcinolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The effects of VS with Hylan G-F 20 and triamcinolone alone and in combination were also compared. In one study, this combination improved pain, mainly in the first week after infiltration (9), while in another study, the improvements in the functional scores lasted up to three months (27). Another study involving 47 patients showed that the same combination improves subjective pain and function (28).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of VS with Hylan G-F 20 and triamcinolone alone and in combination were also compared. In one study, this combination improved pain, mainly in the first week after infiltration (9), while in another study, the improvements in the functional scores lasted up to three months (27). Another study involving 47 patients showed that the same combination improves subjective pain and function (28).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly high patient satisfaction can be expected when using “complete joint space collapse” as indication for TKA surgery. In the case of incomplete joint space collapse, further conservative therapy [21, 24] or joint preserving knee surgery [25] might be considered an alternative to TKA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomised clinical trial demonstrated improvement of pain and function in patients with severe OA of the knee. 28 Waddel et al 29 found that total knee arthroplasty was delayed by more than 7 years in 75% of 1863 knees with grade IV osteoarthritis (1342 patients) who had used viscosupplementation. The European Consensus 23 also states that viscosupplementation may be beneficial in cases of severe osteoarthritis of the knees.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding advanced stages of knee osteoarthritis, although the use of VS as an alternative to a knee prosthesis is not an ideal indication, it can bring benefits to those patients who cannot or do not wish to undergo total knee arthroplasty surgery. 23 , 28 …”
Section: Discussionmentioning
confidence: 99%